Familial predisposition to anterior cruciate ligament injury - Kenichi Goshima; Katsuhiko Kitaoka; Junsuke Nakase; Hiroyuki Tsuchiya (Elsevier, 2014)
Although several risk factors for anterior cruciate ligament (ACL) injury have been evaluated in the literature, there are few reports on familial predisposition. This study investigated the familial predisposition to ACL injury. The study included 350 patients who underwent ACL reconstruction between January 2005 and September 2008. All patients were surveyed by telephone or a written questionnaire about family history (FH) of ACL injury, sports played by family members, and mechanisms of injury. We also compared age, sex, height, weight, body mass index, Tegner activity score, general joint laxity, and tibial slope between an FH group (with FH) and a control group (without FH). In addition, we compared the incidence of ACL graft rupture and contralateral ACL rupture 2 years after primary surgery. Complete information was obtained from 316 patients, 38 (12.0%) of whom had FH of ACL injury. Two families had three members with ACL injuries. Of the 40 family members with ACL injuries, 38 (95%) had noncontact injuries and 34 (85%) shared a similar mechanism of injury with the related patient. No significant differences were identified between the two groups, except that tibial slope was significantly greater in the FH group than in the control group. Although the incidence of repeat ACL injury was greater in the FH group (23.7%) than in the control group (16.4%), there was no significant difference. Our results indicated a high probability of familial predisposition to many of the identified risk factors for ACL injury. In addition, patients with FH of ACL injury might be at high risk for initial and repeat ACL injuries. Therefore, prevention programs should be implemented for patients with FH of ACL injury in order to decrease the risk of these injuries.